Rich but underappreciated. Žižkov and normalization in Simona Bohata's prose Everyone is embarrassing - Šidáková Fialová, Alena (Bohemica Olomucensia, 2023)
The study is devoted to Simona Bohatá's second prose book Všichni sou trapný (Everybody is Embarrassing). In the context of the evaluation of the novel, the study reflects more generally on the popularity of books with the theme of normalization. We can see a certain decline of interest in this topic in recent years as one of the reasons why Simona Bohatá's prose is not very successful among readers, despite the positive reviews and its undoubted literary qualities.
Keywords: Simona Bohatá; normalization; Žižkov; contemporary Czech prose